THE COMPARISON OF SOCIAL NETWORKS BETWEN YOGYANESE AND SURABAYANESE THROUGH PARABAN NAME (Perbandingan Jaringan Sosial Antara Masyarakat Yogyakarta dan Masyarakat Surabaya melalui Nama Paraban) - Estuningtyas Mahanani (SAWERIGADING, 2021)
AbstractParaban name becomes an important part of the collective system of Javanese culture which is still widely found today and lives as part of the Javanese oral tradition. Each region has its uniqueness of paraban name that can be used in showing the social network of an individual. However, less focus has been placed on the comparision of social network between two regions. Regarding this issue, this study was intended to discover the comparision of social network between Jogjanese and Surabayans through paraban name. In order to collect the data, descriptive qualitative design by using semi-structured interview was used. A number of 5 native Jogjanese and 5 native Surabayans were included in this study.  The data were analyzed and interpreted through qualitative procedures within 3 steps; data condensation, data display, and conclusion. The result of the study showed that the use of paraban name can show the closeness of individual relationship in their community. It also revealed that there were some differences related to social network between Jogjanese and Surabayans. This study suggested that vernacular language should be preserved as a part of national identity and linguistics uniqueness which can be used to study various problems which related to language.